Radio, campo cultural y mediaciones. Apuestas y propuestas para pensar la radio en León - Héctor Gómez Vargas (Estudios sobre las Culturas Contemporáneas)
How to cany out the historical reconstniction of radio in provincial areas? Taking into account the personal experiences, representations and practices of the social actors connected with radio, the studies to be done here should consider the historical context of the place, the everyday dynamics of the subjects and the pattern of access to technological advances.